AN ANALYSIS OF VERBAL AND VISUAL SIGNS IN ADIDAS'S ADVERTISEMENT "READY FOR SPORT" - Ayu Kartika Dewi Ni Ketut (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2021)
This study is entitled “An Analysis of Verbal and Visual Signs in Adidas’s Advertisement “Ready for Sport”. The aims of the study are two identify the verbal and visual signs as well as to analyze their meanings in Adidas’s Advertisement “Ready for Sport”. The data of this study were taken from Adidas official website since the advertisement showed combination between colors, picture, and words. The process of collecting data was conducted by observation method and note taking technique. The data were analyzed descriptive qualitatively. The researcher used theory of semiotics from Saussure as citied by Chandler (2007), theory of meaning from Barthes (1967) and supported by theory of color from Wierzbicka (1996) to answer the research problem.  Through the analysis, it found that verbal and visual signs have important rules to make an attractive advertisement. These verbal and visual signs contain denotative and connotative meaning. The advertiser tends to use expressive and informative function to express their idea and give information about the product to attract the reader’s attention. Both of verbal and visual signs are related to each other since what is in verbal sign are conveyed in visual signs. They support each other to makes good combination in an advertisement.